2010
DOI: 10.1163/000579510x504879
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crowding and density on male mating behaviour in the rose bitterling (Rhodeus ocellatus)

Abstract: Female density and resource availability are two key variables that shape mating systems. Theory predicts that reproductive skew will amplify with increased male density and decreasing availability of resources, though limited empirical evidence suggests that this may not always be the case. Here we tested mean crowding, defined as the number of males per unit of resource, and density per se, defined as the number of individuals present per unit area, to investigate their effect on the mating system of Rhodeus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A prediction from our results is that those males suited to a guarder role will have greater reproductive success at low densities, where the reproductive success of guarder is known to be greatest [16,26]. By contrast, males with superior cognitive ability would be predicted to perform better at high male densities, where sperm competition and male ability to optimally distribute their ejaculates plays a more critical role in male reproductive success [16,26,36,46,47]. A predicted outcome is that selection on male cognitive traits will vary among populations, and within populations rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…A prediction from our results is that those males suited to a guarder role will have greater reproductive success at low densities, where the reproductive success of guarder is known to be greatest [16,26]. By contrast, males with superior cognitive ability would be predicted to perform better at high male densities, where sperm competition and male ability to optimally distribute their ejaculates plays a more critical role in male reproductive success [16,26,36,46,47]. A predicted outcome is that selection on male cognitive traits will vary among populations, and within populations rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 77%
“…The mechanism by which spatial cognition might contribute to male reproductive success was not directly measured in this study. However, male reproductive success in bitterlings is closely linked to the way the male distributes ejaculates in space and time, particularly for sneakers [16,17,26,36,37]. In nature and in the laboratory, male bitterlings systematically patrol mussels in rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors that control these differences are numerous. In fish, sexual selection (Casalini et al, 2010), parental care (Dupont Cyr et al, 2018), niche separation (Gerritsen et al, 2010), and feeding characteristics (type of food, food intake, food conversion efficiency, search for food, and vulnerability to predators; Blair Holtby and Healy, 1990; Rennie et al, 2008;Horppila et al, 2011) have all been shown to influence SSD.…”
Section: Introductionmentioning
confidence: 99%